Pengabdian Kepada Masyarakat Melalui Kegiatan Pembersihan Rumah Ibadah Bersama Pengurus Paguyuban Ika Pakarti Kutai Timur - Eka Widyanti; Muhammad Yasin (MAYARA: Jurnal Pengabdian Masyarakat, 2023)
Lack of public awareness to carry out mutual cooperation is a reality that is often found in urban communities. One of the concerns of this dedication is the cleanliness of the house of worship (mosque). This service is carried out through collaboration between the Islamic Religious Education Study Program (PAI) and the DPD Ika Pakarti, East Kutai Regency. The PAI Study Program was represented by 2 lecturers and the DPD Ika Pakarti was represented by 25 members of the association. Implementation This activity was carried out at the Al-Abror Mosque, Jln. Kenyamukan North Sangatta East Kutai Regency, the implementation of the action was carried out in mutual cooperation on Sunday from 08 to 11.00 WITA, namely on February 5 2023 The method used is the Participatory Action Research method, where the call participants are directly involved in the process of cleaning the house Worship (mosque). The result is that community service through cleaning houses of worship (mosques) gets extraordinary enthusiasm. This can be seen from the increasing number of people participating. Another result of this service is an increase in the cleanliness of the mosque after carrying out community service.